Analisis Nutrisi dan Daya Terima Konsumen terhadap Mie Ubi Jalar (Ipomoea batatas L) Berfortifikasi Rumput Laut Gracilaria sp - Deserlia, Viva; Karim, Mutemainna; Jumrawati, Jumrawati (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2024)
Making sweet potato noodle products with Gracilaria sp. seaweed fortification is one of the efforts to provide gluten-free products that are good for health and help the community optimize the selling value of seaweed. This study aims to determine the effect of Gracilaria sp. seaweed fortification on the nutritional value of protein content, water content, and gluten content of sweet potato flour and to determine consumer acceptance of sensory quality in sweet potato noodles (Ipomoea batatas L) fortified with Gracilaria sp. seaweed. This study was conducted in May-July 2024 at the Pangkep State Agricultural Polytechnic Biochemistry Laboratory. This study used an experimental method with a Completely Randomized Design (CRD). The parameters tested in this study were protein content, water content, gluten content of sweet potato flour, and sensory quality, namely: appearance, aroma, texture, and taste. Data analysis of protein content, water content, and sensory quality were analyzed using ANOVA. The results of the study showed that the highest protein content of 3.86% was found in seaweed-fortified sweet potato noodles with a concentration of 10% and the lowest protein content of 3.04% was found in seaweed-fortified sweet potato noodles with a concentration of 0% and the highest water content of 13.19% was found in seaweed fortified sweet potato noodles with a concentration of 10%. The lowest value was 11.55% The conclusion is that Gracilaria sp. seaweed fortification has a significant effect on the Nutritional Value of sweet potato noodles. The sensory quality values ​​for color, aroma, and taste with a concentration of 5% are preferred by consumers.